Scrutinizing the role of learning analytics in Malaysian higher education through the lens of TVET - Omar, Nurul Ihsaniah (Universiti Teknologi MARA, Kedah, 2024)
TVET colleges can provide tertiary education and training and a road to good jobs. TVET higher education emphasises technical, vocational, and occupational training to prepare students for skilled trade work. Due to fast-paced industries and creative educational methods, Learning Analytics (LA) was created to meet TVET higher education teaching and learning issues. Several researchers have synthesised data to analyse LA concerns in higher education, particularly TVET. A comprehensive literature review examined LA's benefits in TVET higher education. Students, educators, and institutions benefit most from LA. Despite being a novel idea, TVET higher education stakeholders need to understand LA's benefits. A comprehensive explanation of LA's benefits allows TVET higher education stakeholders to use LA to improve teaching and learning.